2013
DOI: 10.1371/journal.pone.0073235
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibition Promotes Parkin-Ubc13 Interaction and Lysine 63-Linked Ubiquitination

Abstract: Disruption of the ubiquitin-proteasome system, which normally identifies and degrades unwanted intracellular proteins, is thought to underlie neurodegeneration. Supporting this, mutations of Parkin, a ubiquitin ligase, are associated with autosomal recessive parkinsonism. Remarkably, Parkin can protect neurons against a wide spectrum of stress, including those that promote proteasome dysfunction. Although the mechanism underlying the preservation of proteasome function by Parkin is hitherto unclear, we have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
(63 reference statements)
3
25
0
Order By: Relevance
“…Accumulating evidence indicates that, when the proteasome is impaired, misfolded proteins are actively transported to the perinuclear region to form an aggresome, which is thought to be a cytoprotective mechanism for sequestering misfolded proteins and reducing their cytotoxicity [2729]. We found that K63-linked polyubiquitination of SOD1 mutant proteins by parkin is enhanced in response to proteasome impairment, consistent with recent reports that the E3 ligase activity of parkin to recruit UbcH13/Uev1a and catalyze K63-linked polyubiquitination is stimulated by proteasome inhibition [35, 66]. Our data provide evidence that parkin-mediated K63-linked polyubiquitination of SOD1 mutant proteins could occur prior to their transport to aggresomes.…”
Section: Discussionsupporting
confidence: 89%
“…Accumulating evidence indicates that, when the proteasome is impaired, misfolded proteins are actively transported to the perinuclear region to form an aggresome, which is thought to be a cytoprotective mechanism for sequestering misfolded proteins and reducing their cytotoxicity [2729]. We found that K63-linked polyubiquitination of SOD1 mutant proteins by parkin is enhanced in response to proteasome impairment, consistent with recent reports that the E3 ligase activity of parkin to recruit UbcH13/Uev1a and catalyze K63-linked polyubiquitination is stimulated by proteasome inhibition [35, 66]. Our data provide evidence that parkin-mediated K63-linked polyubiquitination of SOD1 mutant proteins could occur prior to their transport to aggresomes.…”
Section: Discussionsupporting
confidence: 89%
“…We therefore sought to systematically and quantitatively examine the chain linkage types produced by PARKIN in vitro. The vast majority of papers examining PARKIN’s UB ligase activity in vitro have used forms of PARKIN that are not activated by PINK1, often employing fragments of PARKIN that lack the UBL domain phosphorylated by PINK1 (Chaugule et al, 2011; Lim et al, 2013; Matsuda, 2006; Trempe et al, 2013; Wauer and Komander, 2013), and in cases where PINK1-dependent activity has been monitored with purified proteins, the reported stoichiometry of phosphorylation at S65 in PARKIN was very low (0.08) (Kazlauskaite et al, 2014a). Thus, the relationship between the activities measured in previous studies and that of near stoichiometrically phosphorylated PARKIN, including the types of UB chains assembled, remain poorly defined.…”
Section: Resultsmentioning
confidence: 99%
“…As a RING-HECT hybrid, the chain linkage types made by PARKIN are thought to be dictated by PARKIN itself. However, prior studies both in vitro and in vivo have painted a bewildering picture of PARKIN chain assembly, with K27, K48, and K63 linked chains being independently reported on various PARKIN targets or on total mitochondrial proteins, most often using overexpressed UB mutants (in vivo) or fragments of PARKIN not activated by PINK1 (in vitro) that are prone to artifacts (Matsuda, 2006; Rankin et al, 2014; Riley et al, 2013; Chan et al, 2011; Geisler et al, 2010; Sims et al, 2012; van Wijk et al, 2012; Lazarou et al, 2013; Lim et al, 2013; Birsa et al, 2014). Thus, it is unclear the extent to which PARKIN is able to build particular types of UB chains on its substrates in vivo with endogenous UB, the extent to which the activation state of PARKIN determines its chain assembly activity, and whether particular PD patient-derived mutants alter chain linkage specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lys-63-linked ubiquitination by Parkin has been suggested to be important for the suppression of protein toxicity by Parkin, further investigations will be required to determine whether specific roles of Lys-63-linked ubiquitination in the PINK1-Parkin pathway exist (37,38).…”
Section: Lc3-mediated Autophagy Machinery (22) To Test Whether Autopmentioning
confidence: 99%